Ocular manifestation and surgical treatment outcomes in Alport syndrome – case series - Ostrowska-Spaleniak, Aleksandra; Krix-Jachym, Karolina; Rękas, Marek (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Alport syndrome is a progressive, genetically determined disease, caused by mutations in the genes coding for type IV collagen biosynthesis. Its clinical manifestation includes a triad of symptoms: haematuria with renal failure, neurosensory hearing loss, and ocular abnormalities. The ocular features of Alport syndrome are anterior lenticonus (pathognomomic), posterior polymorphous corneal dystrophy, recurrent corneal erosions, central or perimacular fleck retinopathy and peripheral coalescing fleck retinopathy, temporal retinal thinning and cataract. No causal treatment of Alport syndrome is currently available; it is only possible to treat local and systemic complications secondary to disease progression. The paper discusses ocular manifestation of Alport syndrome and surgical treatment outcomes in 2 patients. Both patients reported vision impairment for several years. Ocular examination findings included anterior lenticonus and cataract in both patients plus dot-and-fleck retinopathy and temporal retinal thinning in one of them. Anterior lenticonus and cataract were treated with phacoemulsification with intraocular lens implantation, resulting in improved visual acuity in both patients.